Media Experiments with Jumping Word Circles in Improving Arabic Vocabulary Learning for Class IV MI Muhammadiyah Sribit - Rosyidah Dzunur'aini; Naimah (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2021)
Mastery of Arabic vocabulary is the main key to success in learning Arabic. By using media as a bridge in distributing material, it will change the mindset of students who think learning Arabic is difficult to understand. At MI Muhammadiyah Sribit, the conventional Arabic learning process inspired researchers to conduct experimental research on the use of word hoop game media to know the differences in students' Arabic vocabulary mastery between the experimental class and the control class. This study uses a quasi-experimental research type with a quantitative approach. The research subjects were students of class IV A as the experimental class and students of class IV B as the control class. The process of collecting data using test results, observations, and interviews was then analyzed using the paired-sample t-test and independent-sample t-test with the help of SPSS. From the results of the study, it was found that the results of the application of game media in learning Arabic can improve students' vocabulary mastery. Based on the results of the independent sample t-test, the posttest significance value in the experimental class was 0.008 < 0.05, and the posttest value in the control class was 0.009 < 0.05. So it can be concluded that there is a significant difference between the mastery of Arabic vocabulary for the experimental class and the control class. Abstrak: Penguasaan kosa-kata bahasa Arab merupakan kunci keberhasilan utama dalam belajar bahasa Arab. Dengan menggunakan media sebagai jembatan dalam menyalurkan materi akan mengubah pola pikir peserta didik yang menganggap pembelajaran bahasa Arab sulit untuk dipahami. MI Muhammadiyah Sribit dalam proses pembelajaran bahasa Arab yang masih konvensional menginspirasi peneliti untuk melakukan penelitian eksperimen penggunaan media permainan melompat bulatan kata dengan tujuan untuk mengetahui perbedaan penguasaan kosa-kata bahasa Arab peserta didik antara kelas eksperimen dan kelas kontrol. Penelitian ini menggunakan jenis penelitian eksperimen kuasi dengan pendekatan kuantitatif. Adapun subyek penelitian adalah peserta didik kelas IV A sebagai kelas eksperimen dan peserta didik kelas IV B sebagai kelas kontrol. Proses pengumpulan data dengan menggunakan hasil tes, observasi dan wawancara kemudian dianalisis dengan menggukan uji paired sample t test dan independent sample t test dengan bantuan SPSS. Dari hasil penelitian diperoleh hasil bahwa hasil dari penerapan media permainan dalam pembelajaran bahasa arab dapat meningkatkan penguasaan kosa-kata peserta didik. Berdasarkan hasil uji independent sample t test diperoleh nilai signifikasi posttest pada kelas eksperimen sebesar 0.008 < 0.05 dan nilai posttest pada kelas kontrol 0.009 < 0.05. Maka dapat disimpulkan bahwa terdapat perbedaan yang signifikan antara penguasaan ksoa-kata bahasa Arab peserta didik kelas eksperimen dan kelas kontrol. .